PARENTAL EDUCATIONAL LEVEL AND PUPILS’ ACADEMIC PERFORMANCE IN PUBLIC PRIMARY SCHOOLS IN ENDEBESS SUB COUNTY, KENYA - Misiko, Kiplangat Moses; Kirwok, Emily; Kikechi, Ronald Werunga (IJRDO- Journal of Educational Research, 2023)
Thus, the purpose of the study was to assess the influence of parental educational level on pupils’ academic performance in public primary schools in Endebess Sub County, Kenya; establish the influence of family size on pupils’ academic performance in public primary. It adopted a descriptive survey research design, with a target population of 3,072 individuals including all 47 head teachers, 705 teachers, and 2,320 class 8 students. The sample size of 246 participants was determined using the Krejcie & Morgan table (1970). The researcher collected data using questionnaires and interview guides. The instruments were validated by the experts in the area of study. Reliability of the instruments was established, and Cronbach's alpha coefficient was 0.78, indicating the instruments were reliable. Quantitative data was analyzed using descriptive and inferential statistics and presented in tables, while qualitative data analyzed in themes and sub themes and presented using quotations. The study established that parental educational levels influence academic performance in public primary schools. It was therefore recommended that there should be a consideration of home-based management dynamics like parental educational level as they determine pupils’ academic performance in public primary schools. The information provided by this study will benefit policymakers, community members and academicians.